Curcumin-mediated alleviation of dextran-induced leaky gut in Drosophila melanogaster - Khaerani, Mufliha; Chaeratunnisa, Rizkya; Salsabila, Annisa; Asbah, Asbah; Asri, Rangga M.; Shiratsuchi, Akiko; Nainu, Firzan (Narra J, 2024)
Aging is commonly characterized by a decline in the physiological functioning of the body organs, with one hallmark being the impairment of intestinal function, leading to increased intestinal permeability known as leaky gut. The aim of this study was to investigate the potential of curcumin to prevent the development of leaky gut in Drosophila melanogaster utilizing the smurf fly method. In this study, flies aged 3–5 days underwent a 10-day dextran sulfate sodium (DSS) treatment to induce intestinal permeability, followed by a smurf assay using brilliant blue dye and locomotor testing the next day. Flies displaying the smurf phenotype were divided into four groups: untreated control and curcumin-treated (10 µM, 50 µM, and 250 µM). After 21 days of treatment, flies were reassessed for the smurf phenotype and underwent locomotor testing. On day 23, flies were subjected to RT-qPCR analysis. By inducing increased intestinal permeability through the administration of DSS, a higher proportion of flies exhibiting the smurf phenotype and a reduced survival rate in the DSS-treated group were observed. Such phenotypes were reversed, decreased number of flies displaying the smurf phenotype and improved fly survival, upon the incorporation of curcumin in the fly food at concentrations of 10, 50, and 250 µM. Subsequent molecular analysis revealed upregulated expression of sod1, cat, and pepck genes, while no significant changes were observed in the expression of sod2, indy, and srl genes following treatment with curcumin at high concentration. Overall, our findings provide insight into the potential effect of curcumin to alleviate the phenotypical features associated with DSS-induced leaky gut, possibly via the selective regulation of aging-related genes.